MnFe2O4@PANI@Ag Heterogeneous Nanocatalyst for Degradation of Industrial Aqueous Organic Pollutants. Issue 2 (February 2016) - Amir, Md.; Kurtan, U.; Baykal, A.; Sözeri, H.
Graphical Abstract: Abstract : This paper reports a stable heterogeneous nanoparticles catalyst MnFe2 O4 @PANI@Ag for the degradation of azo dyes. In this synthesizing method, MnFe2 O4 is used as magnetic core and polyaniline (PANI) a linker to stabilize the Ag nanoparticles (NPs) on the surface of catalyst. The method has a high ability to prevent Ag NPs from aggregation on the PANI surface, thus resulting in small size and highly dispersed Ag NPs. The composition and nano-structural features of polycrystalline sample were studied by X-ray powder diffractometry, Fourier transform infrared spectroscopy, and scanning electron microscopy. Vibrating sample magnetometer measurements proved the super-paramagnetic property of the catalyst, and UV results demonstrated that MnFe2 O4 @PANI@Ag has a high ability to reduce the azo dyes, which come from industrial wastes in the form of pollutant. The nanocomposites could be readily separated by magnet and reused for the next four reductions with high generation efficiency.